Author’s index of Militaria/ Outeursindeks van Militaria (1969-1984) - Militaria, Editorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
List of Author’s & Titles published in Militaria (1969-1984) / Lys van Outeurs en Titels gepubliseer in Militaria (1969-1984)